The unusual inter-tidal niche of the rare moss Bryum marratii Wilson. (2nd October 2018) - Callaghan, Des A.; Farr, Gareth
Abstract : This is the first detailed ecological investigation of the rare moss Bryum marratii Wilson. Results show occupancy of a niche at the two study sites that is unusual amongst bryophytes, within the upper edge of saltmarsh. All colonies ( n = 120), which comprise the largest populations in Wales, occur in an elevation zone of just 57 cm and are subject to frequent inundation by higher spring tides. In total, the average location of a B. marratii colony was submerged by seawater 3.6 day -1 yr -1 . Sea level rise, projected in the study region to be 30–46 cm during the current century, is a major threat to the long-term survival of these populations.